2006
DOI: 10.1134/s1087659606060149
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced bleaching in Ga-Ge-S(Se) vitreous films

Abstract: Vitreous films in the Ga-Ge-S(Se) system are prepared through pulsed laser deposition and investigated. An analysis of the data of Raman and energy-dispersive X-ray spectroscopy demonstrates that the composition and structure of the films are similar to those of the monolithic glass. Exposure of the films to radiation with an energy higher than the band gap leads to bleaching of sulfur-based films due to the local oxidation of the films as judged from the data of infrared, Raman, and energy-dispersive X-ray sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…al., studied Ge-Sb-S nonoxide glasses and they found that addition of Sb increases linear refractive index, density as well as shift of absorption edge to infrared [11]. Therefore Ge-Sb-S are of interesting glasses for remarkable application as antioxidants over cladding layers of micro-resonator-based sensing [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…al., studied Ge-Sb-S nonoxide glasses and they found that addition of Sb increases linear refractive index, density as well as shift of absorption edge to infrared [11]. Therefore Ge-Sb-S are of interesting glasses for remarkable application as antioxidants over cladding layers of micro-resonator-based sensing [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Stated by A.S Tverjanovicha et al in Ga-Ge-S, energy exposure is greater than that of band gap resulting in the substitution of S by Se leads to photoinduced bleaching and concerning photo-induced darkening. Exposure to energy, Ge20Se72.5Bi7.5 films contributes to a decrease in the optical values of the bandgap [7]. The Ga5Sb10Ge25Se60 glass is very stable for crystallization and has a high temperature transition glass, making it a suitable candidate for the development and manufacturing of IR optical devices [8].…”
Section: Introductionmentioning
confidence: 99%
“…The PD shift is typically stable at room temperature but can be reversed by annealing below the glass transition temperature [7]. A.S Tverjanovicha et al have reported [8] that in Ga-Ge-S, exposure with energy higher than the band gap leads to photoinduced bleaching and the replacement of S by Se brings about photoinduced darkening. In Ge 20 Se 72.5 Bi 7.5 films exposure of above band gap light leads to a decrease in the values of the optical band gap.…”
Section: Introductionmentioning
confidence: 99%